The Impact of Bank Capital on Profitability： An empirical study from China commercial - Ma, Shuxian (2022)
This paper uses multiple regressions to understand the impact of different definitions of capital on bank profitability by using a fixed effects model to analyse data from Chinese commercial banks for the period 2013 to 2020. This study finds that capital has a positive effect on bank profitability when measured by return on average assets, with banks' profitability increasing significantly as the equity-to-assets ratio and capital adequacy ratio increase. Regardless of how bank profitability is measured, the equity asset ratio is positively associated with bank profitability. The Tier 1 capital ratio has a significant negative impact on the NIM of Chinese commercial banks, implying that banks raising their own capital to cope with risk does not improve their profitability. Therefore, Chinese commercial banks should pay attention to the type of capital absorbed when making their profits greater by adjusting their capital structure. Increasing the bank's capital adequacy ratio back to enhance bank profitability, while increasing the Tier 1 capital ratio will instead reduce the bank's profitability.